Some estimated effects of the planned harnessing of the Ounasjoki river on reindeer husbandry - Nieminen, Pirkko; Nieminen, Mauri (Rangifer, 1983)
The harnessing of waterways for electrical power has caused permanent pasture losses and prevented the free movement of the reindeer herds in Finland. Many great changes occurred after construction of the two large artificial lakes of Lokka and Porttipahta (total 630 km2) in the Lappi reindeer herders association in the 1960s. The planned harnessing of the Ounasjoki river consists of 10 power plants and 2 big and 12 smaller artificial lakes (total 270 km2). The plan will have effects on the income of 1070 owners in 7 reindeer herders associations. The losses in reindeer husbandry estimated by three different methods were maximally 476, 2824 and 9900 reindeer (value of meat production 0.12 to 2.5 million FIM/year), 64 jobs and various herding buildings (value 3.9 million FIM). Two new reindeer farmes would become unusuable (0.5 million FIM) and in addition hay production from seasonally flooded fields (approx. 25 000 - 30 000 FIM/year) would be lost. The building of new forces in the reindeer herders association areas of Ounasjoki river would require 6.2 million FIM.Ounasjoen rakentamissuunnitelman mahdolliset vaikutukset porotalouteen.Abstract in Finnsish / Yhteenveto: Vesistojen valjastaminen såhkontuottoon on tuhonnut porolaitumia ja vaikcuttanut porojen vapaata liikkumista Suomessa. Tasta on hyvånå esimerkkinå Lokan ja Portipahdan tekoaltaiden (yhteenså 630 km2) rakentaminen Lapin paliskunnassa 1960-luvulta alkacn. Ounasjoen rakentamissuunnitelma kåsittåå 10 voimalaitosta ja 2 isoa ja 12 picnempåå tekoallasta (yhteenså 270 km2). Rakennussuunnitelma vaikuttaa 1070 poronomistajan talouteen 7 cri paliskunnassa. Kolmella eri mcnetelmallå laskien jouduttaisiin enimmillåån våhentåmåån 476, 2824 ja 9900 lukuporoa (lihantuotto 0,12-2,5 milj. mk/vuosi) sekå menetettåisim 64 ympårivuotista tyopaikkaa ja kocttaisiin useita eri rakennevahinkoja (arvoltaan noin 3,9 milj. mk). Kaksi uutta porotilaa jåisi kåyttokclvottomiksi (0,5 milj. mk) ja lisaksi tulvaniittyjen hcinåtuotto (noin 25 000 — 30 000 mk/vuosi) menetettåisiin. Uusicn estcaitO|en rakentamiseen tarvittaisiin Ounasjoki-alucen paliskunnissa 6,2 milj. mk.Ounasjoki-projektets eventuella foljder på renskotseln.Abstract in Swedish / Sammandrag: Vattendragens uttnytjande for production av el-kraft har forstord renbetesmarker och forsvårat renarnas mojlighet att rora sig fritt i Finland. Som exempel hårav må nåmnas byggnadsprojekten for Lokka och Porttipahta regleringsreservoarer (inalles 630 km2) fr.o.m. borjan av 1960-talet inom Lappi renbeteslag. Ounasjoki-projektet omfattar 10 kraftverk samt 2 stora och 12 mindre reservoarer (inalles 270 km2). Byggnadsprojektcts influensområde skulle omfatta 1070 renågarens hushåll inom 7 renbeteslag. Genom att anvånda tre olika råkncsått kommer man till ett resultat, att man skulle bli tvungen att forminska maksimalt 476, 2824 och 9900 renar (ett kottproduction på ca. 0.12-2.5 million FIM/år) och skulle mista 64 året rundt anvåndbara arbetsplatser och dessutom bli lidande av flere olika slags damage (forstorda stångslen osv.) med ett varde på ca. 3.9 million FIM. Två rcncgendomar skulle bli f5rstorda (0.5 million FIM) och dessutom skulle man forlora flodångarnas hoskord (25 000 - 30 000 PTM/år). Inom Ounasjoki-områdets renbeteslag skulle man behova 6.2 million FIM for uppråttande av nya stångsel på området.